CHONDROID HAMARTOMA AS AN UNCALACIDIED MASS AN UNUSUAL PRESENTATION - Nafees, Col Muhammad; Majeed, Farhan Ahmad; Rehman, Asif (Pakistan Armed Forces Medical Journal, 2010)
Chondroid hamartomas of the lungs are uncommon lesions which are usually solitary, small-sized, calcified and peripherally located. They are usually asymptomatic and are detected incidentally on chest X-ray or at autopsy. Rarely, they may be large in size and may clinically mimic malignancy1,2. They are rare benign lesions of the lung comprising 8% of all lung tumors3. Herein, we describe a case of pulmonary chondroid hamartoma presenting as an uncalcified mass which clinically mimicked bronchogenic carcinoma